Making CGIAR Evaluations Gender Responsive and Inclusive: Integrating Gender Equality Youth and Social Inclusion (GEYSI) & Gender Diversity and Inclusion (GDI) - CGIAR Independent Advisory and Evaluation Service (2025)
SC23-12v